The Relationship between Investor Behaviours with Fatwa Coordination of Amanah Saham Nasional (ASN) and Amanah Saham Bumiputera (ASB) - Zamzuri, Zamzuri; Yaacob, Salmy Edawati; Mahmud Zuhudi, Nurulashiqin (Samarah: Jurnal Hukum Keluarga dan Hukum Islam, 2023)
The fatwas coordination of Amanah Saham Nasional (ASN) and Amanah Saham Bumiputera (ASB) in 2017 revealed a subsequent growth in the number of ASB shareholders. To the extent that there is a connection between investor behaviors and the coordination of fatwas in making investment decisions. The systematic literature study also proves the inconsistency of fatwa studies, especially concerning human behaviour based on the sharia. Numerous studies have been done on how religion affects conduct, but they do not specifically refer to a fatwa when they address religion. In order to break the current gap, this paper investigates how the coordination of fatwas in Malaysia affects the behavior of Amanah Saham Nasional (ASN) and Amanah Saham Bumiputera (ASB) investors. A total of 452 samples were descriptively and inferentially analyzed using SPSS utilizing a series of questionnaires given through Google Forms to ASN and ASB investors. The findings indicate that the correlation coefficient for behavior variables is 1,000, whereas the correlation value for fatwa variables is 0.460. The Spearmen Table reveals a relatively significant relationship between investor behaviors variables and fatwa variables that correlate linearly. These findings show that ASN and ASB investors consider fatwa variables in their investment decisions, which influences financial service providers, fatwa institutions, and the community, particularly in terms of addressing fatwa inconsistency for the sake of the ummah. The implications of this research focus on showing the beneficial role of religious organizations in the country's economic growth. It also highlights the concern of financial service providers in fulfilling the community's demands in accordance with Islamic law.